Self-palpation for detection of paroxysmal atrial fibrillation: much noise with little signal - Rahimi, K; Kirchhof, P (Public Library of Science, 2020)
Kazem Rahimi and Paulus Kirchhof discuss the latest work from Faris Ghazal et al and how it may impact the way we currently detect Atrial Fibrillation in the general population.